Character Building: Telaah Pemikiran Ibnu Miskawaih tentang Pendidikan Karakter - Hariyanto , Hariyanto; Anjaryati, Fibriana (Program Pascasarjana Universitas Ibrahimy, 2016)
One of the figures of the Islamic philosopher that concern to talk about morals is Ibn Maskawaih. He is known in the world of philosophy as a man who became the center of attention of the Islamic-authors. In addition, he is also known as a great poet, physician, historian, and chemist. The shift of learner values, the changes of behavior, the character and pattern of teacher and student interaction becomes important to refer back to Ibn Maskawaihs’ thinking about how to make morality as the basis of mental development and behavior